MBCT (Mindfulness Based Cognitive Therapy) terhadap Stres dan Kopingsindrom Pramenstruasi - Jauhary, Ermilya Restiani; Sumarni, Sri; Arwani, Arwani (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of MBCT (Mindfulness Based Cognitive Therapy) intervention on stress and coping with premenstrual syndrome. The research method is a quasi-experiment within two groups with a pretest-posttest control group design. The results showed that the Mindfulness-Based Cognitive Therapy (MBCT) Intervention affected stress (p 0.000 <0.015) and had an effect on coping with premenstrual syndrome (P 0.049 <0.05) compared to the control group. The conclusion is that the Mindfulness-Based Cognitive Therapy (MBCT) Intervention has an effect on stress and coping with premenstrual syndrome for four weeks consisting of 4 meeting sessions with a duration of 60 minutes per meeting so that it can be applied as an alternative holistic therapy for sufferers of premenstrual syndrome. Keywords: Coping with Premenstrual Syndrome, MBCT, Premenstrual Syndrome, Stress